A Cross-Sectional Study Assessing Depression and Associated Healthcare Barriers among Urban Pakistani Women - Marina Haque; Alina Haque; Allysha Choudhury; Roland Alexander Blackwood (Masters Program in Public Health, 2020)
Background: Few studies have assessed depression amongst Pakistani women, particularly in more upscale communities where many traditional risk factors for depression and associated treatment are greatly reduced. Therefore, this study sought to examine depression prevalence in a highly developed sector of Islamabad, factors associated with depression, and the association between depression and barriers to accessing healthcare.Subjects and Method: In 2016, a cross-sectional pilot study was conducted in Islamabad using convenience sampling. The survey design was based on the Pakistan Demographic Health Survey and included the Center for Epidemiological Studies Depression (CESD) scale. 93 women filled out the entire questionnaire.Results: The prevalence of depression was unanticipated at 78%; 53% of these women sampled had major depression. 22% of women reported ever having spoken to a provider about their mental health. 41% of women further reported that their mental health negatively impacted their decision to receive care. The only independent risk factor for depression was the diagnosis of another disease. Indicators of poor-socioeconomic status, however, were consistently associated with higher depression likelihood. A robust multivariable regression analysis showed an association between a higher number of self-reported barriers to accessing care and higher depression scale scores (p<0.05).Conclusion: A high burden of untreated depression likely exists amongst Pakistani women from urban regions despite a relatively higher prevalence of healthcare resources. Improving mental health disparities in urban settings throughout Southwest and South Asia will require not only increased screening and treatment of patients, but also removal of physical and psychological barriers faced in accessing care.Keywords: mental health, access barrier, women